العادات والتقاليد والمعتقدات في رواية مملكة الزيوان لحاج أحمد الصديق - رابح, زهراء (جامعة الوادي - University of Eloued, 2020)
ملخص: رواية مملكة الزيوان لحاج أحمد الصديق واحدة من الروايات الصحراوية الغنية بتوظيف التراث الشعبي، الذي يعكس واقع الحياة الثقافية والاجتماعية والعلمية لأهل توات . ومن خلال هذا البحث سنقف على بعض العادات والتقاليد والمعتقدات عند أهل توات؛ لنبين أبعادها ودلالاتها التراثية، ومدى تمسك أهل المنطقة بها، وقد بلغ إيمانهم بها حدا جعل بعضهم يخالف حتى الشّرع كممارسة طقوس السّحر. كما أنّ بعضها ما زال يمارس لحد السّاعة على الرّغم من الجهود الإصلاحية التي بذلها رجال العلم والإصلاح؛ نظرا لسلطان العادة، وعدم تبلور المفهوم الصّحيح للعبادة، هذا مع التّأكيد على الجانب الإيجابيّ لبعض العادات والتّقاليد الحسنة في ضمان تماسك النّسيج الاجتماعيّ ودورها الكبير والفعّال في الحفاظ على ذاكرة الشّعوب وتراثها. كلمات مفتاحية: العادات؛ التقاليد؛المعتقدات؛ مملكة الزيوان؛ الصّحراء؛ توات Abstract : Elhadj Ahmed Essaddik’s novel « Mamlakat Ezziouan » is one of the saharian novels that is rich of using popular heritage which reflects the reality of cultural , social and scientific life of Touat population . Through this research we will see some customs , traditions and believes of Touat people . In doing so , we aimed at identifyig its concepts and how important they were as cultural heritage and how much people of this region are failhful to them . as they strongly believers of those concepts , they sometimes contradict and violate relegious regulations as believing in magic . The majority of them are still practising magic nowadays. Even though they were very old actions . Inspite of the remedial efforts that were made by the scientists , because of the dominance of traditions and the ambiguity of the concept worship , this of course was the positive side of some useful habits and traditions to ensure the unification of the community and its effective contribution to preserve the societies memories and cultural heritage . Keywords : habits; customs; believes; Mamlakat Ezziouan; the Sahara; Touat .
مقال
Keywords: العادات؛ التقاليد؛المعتقدات؛ مملكة الزيوان؛ الصحراء؛ توات